Driving Green: The Role of Social Media eWOM and Planned Behavior in Electric Vehicle Purchase Intentions - Ahmad Zaky; Maya Asria (Al-Qalam Institue, 2026)
This study aims to investigate the influence of attitudes toward social media eWOM information, subjective norms, and perceived behavioral control on consumers’ purchase intention for the Hyundai Ioniq electric vehicle in Padang City. The study is motivated by the rapid growth of Indonesia’s electric vehicle market and the increasing role of digital information in shaping consumer behavior, highlighting a need to understand the psychological and social determinants of purchase intention. A causal research design was employed, using a purposive sampling technique to survey 190 respondents through an online questionnaire distributed via Google Forms and social media platforms. Data were analyzed using multiple linear regression, including validity, reliability, and classical assumption tests. The results indicate that subjective norms and perceived behavioral control significantly and positively affect purchase intention, while attitudes toward social media eWOM information do not have a significant impact. Furthermore, the three variables collectively explain 23% of the variance in purchase intention, suggesting that other contextual and economic factors may also contribute. The study contributes theoretically by confirming the applicability of the Theory of Planned Behavior in an emerging EV market and practically by informing marketing strategies and policy interventions. Future research should expand the geographic scope and incorporate additional mediating variables.